Pengaruh Return on Asset dan Environmental Policies Terhadap Firm Value dengan Green Reputation Sebagai Variabel Moderasi - Lestari, Dwi Indah; Sinta, Siti (Cattleya Darmaya Fortuna, 2024)
This study aims to determine the effect of Return on Asset and Environmental Policies on Firm Value with Green Reputation as a moderating variable of sector consumer non-cyclicals Companies listed on the Indonesia Stock Exchange for the 2017-2021 Period. This research is a quantitative study and uses secondary data. The sampling technique used in this research is purposive sampling technique, with a total sample of 7 companies and 5-year period of observation, totaling 35 samples. The data analysis techniques used in this research are multiple linear regression analysis and moderating regression analysis. The results of this study partially show that Return on Asset has a positive significant effect on Firm Value, Environmental Policies has no significant effect on Firm Value, and green reputation has no significant effect on Firm Value. Meanwhile, green reputation can moderate the relationship between Return on Asset, Environmental Policies, and Firm Value.